2014
DOI: 10.3382/ps.2013-03710
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Salmonella Enteritidis virulence factors to intestinal colonization and systemic dissemination in 1-day-old chickens

Abstract: Salmonella enterica serovar Enteritidis is one of the most common serovars associated with poultry and poultry product contamination in the United States. We previously identified 14 mutant strains of Salmonella Enteritidis phage type 4 (PT4) with significantly reduced invasiveness in human intestinal epithelial cells (Caco-2), chicken macrophages (HD-11), and chicken hepatocellular epithelial cells (LMH). These included Salmonella Enteritidis mutants with transposon insertions in 6 newly identified Salmonella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Allen-Vercoe and Woodward (1999) also reported that afimbriate mutants of SE were not impaired in colonization of the GI tract or internal organs or fecal shedding in orally infected 1-day-old chickens. We reported that disruption of csgB in SE impaired invasiveness in chicken liver cells, but did not significantly impact intestinal colonization and internal organ invasiveness in orally challenged 1-day-old chickens (Addwebi et al, 2014;Shah et al, 2012b). Similarly, inactivation of stdA in SE was reported to result in reduced colonization of cecum as well as less invasion of the internal organs in orally inoculated 7-day-old chickens (Shippy et al, 2013).…”
Section: Genetic Basis Of Gastrointestinal Infection In Chickensmentioning
confidence: 88%
See 4 more Smart Citations
“…Allen-Vercoe and Woodward (1999) also reported that afimbriate mutants of SE were not impaired in colonization of the GI tract or internal organs or fecal shedding in orally infected 1-day-old chickens. We reported that disruption of csgB in SE impaired invasiveness in chicken liver cells, but did not significantly impact intestinal colonization and internal organ invasiveness in orally challenged 1-day-old chickens (Addwebi et al, 2014;Shah et al, 2012b). Similarly, inactivation of stdA in SE was reported to result in reduced colonization of cecum as well as less invasion of the internal organs in orally inoculated 7-day-old chickens (Shippy et al, 2013).…”
Section: Genetic Basis Of Gastrointestinal Infection In Chickensmentioning
confidence: 88%
“…We reported that impaired secretion of flagellar proteins (FlgK, FljB, and FlgL) among wild-type strains of SE was associated with a low-invasive phenotype in chicken macrophages (Shah et al, 2011). We also reported that disruption of the fljB results in reduced invasiveness of SE in cultured chicken liver cells and reduced colonization of the small intestine in orally inoculated day-old chickens (Addwebi et al, 2014;Shah et al, 2012b). Shippy et al (2014) reported that deletion of flgC, encoding the flagellum basal body protein, resulted in significantly reduced colonization of liver and spleen in orally infected 1-week-old chickens.…”
Section: Genetic Basis Of Gastrointestinal Infection In Chickensmentioning
confidence: 91%
See 3 more Smart Citations